2011
DOI: 10.2169/internalmedicine.50.5215
|View full text |Cite
|
Sign up to set email alerts
|

Iliopsoas Hematoma in Gaucher's Disease

Abstract: Gaucher's disease is an autosomal recessive inherited disease characterized by oraganomegaly, cytopenia and bone destruction. Clotting disorders and platelet dysfunctions are described. We report the case of a 22-year-old man who presented subacute groin pain due to spontaneous iliopsoas hematoma. Laboratory investigations found moderate thrombocytopenia, normal coagulation factor activities and unspecific platelet function test disturbances. His spleen was moderately enlarged and no significant bone lesions w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…(c) T1-weighted image shows iso-high-mixed masses extending into the surrounding soft tissues on both sides of the sacral roots, consistent with hematoma. (d) T2-weighted image shows the masses become slightly heterogeneous Jmoudiak et al 2003;Lesić et al 2006;Selton et al 2011). Horev et al reported that MRI examination revealed an unexpected high intramedullary as well as subperiosteal signal, suggesting a subacute hemorrhage or hematoma in five Gaucher disease patients (Horev et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…(c) T1-weighted image shows iso-high-mixed masses extending into the surrounding soft tissues on both sides of the sacral roots, consistent with hematoma. (d) T2-weighted image shows the masses become slightly heterogeneous Jmoudiak et al 2003;Lesić et al 2006;Selton et al 2011). Horev et al reported that MRI examination revealed an unexpected high intramedullary as well as subperiosteal signal, suggesting a subacute hemorrhage or hematoma in five Gaucher disease patients (Horev et al 1991).…”
Section: Discussionmentioning
confidence: 99%
“…However, post-operative [ 52 , 53 , 54 ], delivery, and post-partum bleeding [ 55 , 56 ] have been also reported. In addition to these typical bleeding manifestations of primary hemostasis defects, hemorrhages characteristics of coagulation defects, such as spontaneous Iliopsoas hematomas, have also been reported [ 57 ].…”
Section: Gd and Bleedingmentioning
confidence: 99%
“…A rare subcategory of retroperitoneal hemorrhages is iliopsoas hemorrhage [2]. According to literature, spontaneous iliopsoas hemorrhage has been reported in patients with bleeding diathesis due to congenital or acquired pathology of coagulation, such as hemophilia and von Willebrand disease; in patients on anticoagulant or antiplatelet treatment and secondary to diseases that interfere with coagulation (Dengue hemorrhagic fever, Gaucher disease and Waldenström's macroglobulinemia) [3][4][5][6][7][8]. Hematomas are usually unilateral; never the less bilateral hematomas have been reported in patients on anticoagulant therapy [9][10][11].…”
Section: Introductionmentioning
confidence: 99%